Deep sternal wound infection and pectoralis major muscle flap reconstruction: A single-center 20-year retrospective study - Chen, Chen; Gao, Yu; Zhao, Demei; Ma, Zhouji; Su, Yunyan; Mo, Ran (Frontiers in Surgery, 2022)
Background One of the most drastic complications of median sternal incision is deep sternal wound infection (DSWI), as it can lead to prolonged hospitalization, increased expected costs, re-entry into the ICU and even reoperation. Since the pectoralis major muscle flap (PMMF) technique was proposed in the 1980s, it has been widely used for sternal reconstruction after debridement. Although numerous studies on DSWI have been conducted over the years, the literature on DSWI in Chinese population remains limited. The purpose of this study was to investigate the clinical characteristics of DSWI in patients and the clinical effect of the PMMF at our institution. Methods This study retrospectively analyzed all 14,250 consecutive patients who underwent cardiac surgery in the Department of Cardiothoracic Surgery of Drum Tower Hospital from 2001 to 2020. Ultimately, 134 patients were diagnosed with DSWI.,31 of whom had recently undergone radical debridement and transposition of the PMMF in the cardiothoracic surgery or burns and plastic surgery departments because of DSWIs, while the remaining patients had undergone conservative treatment or other methods of dressing debridement. Results In total, 9,824 patients were enrolled in the study between 2001 and 2020, of whom 134 met the DSWI criteria and 9690 served as controls. Body mass index (OR = 1.08; P = 0.02; 95% CI, 1.01∼1.16) and repeat sternotomy (OR = 5.93; P < 0.01; 95% CI, 2.88∼12.25) were important risk factors for DSWI. Of the 134 patients with DSWI, 31 underwent the PMMF technique, and the remaining 103 served as controls. There were significant differences in coronary artery bypass grafting (CABG) (P < 0.01), valve replacement (P = 0.04) and repeat sternotomy (P < 0.01) between the case group and the control group. The postoperative extubation time (P < 0.001), ICU time (P < 0.001), total hospitalization time (P < 0.001) and postoperative hospitalization time (P < 0.001) in the PMMF group were significantly lower than those in the control group. The results of multivariate regression analysis showed that PMMF surgery was an important protective factor for the postoperative survival of DSWI patients (OR = 0.12; P = 0.04; 95% CI, 0.01∼0.90). Conclusions Staphylococcus aureus was the most common bacteria causing DSWI, which was associated with BMI and reoperation, and can be validly treated with PMMF.